5(s+2)=7(s-1)

Simple and best practice solution for 5(s+2)=7(s-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(s+2)=7(s-1) equation:


Simplifying
5(s + 2) = 7(s + -1)

Reorder the terms:
5(2 + s) = 7(s + -1)
(2 * 5 + s * 5) = 7(s + -1)
(10 + 5s) = 7(s + -1)

Reorder the terms:
10 + 5s = 7(-1 + s)
10 + 5s = (-1 * 7 + s * 7)
10 + 5s = (-7 + 7s)

Solving
10 + 5s = -7 + 7s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-7s' to each side of the equation.
10 + 5s + -7s = -7 + 7s + -7s

Combine like terms: 5s + -7s = -2s
10 + -2s = -7 + 7s + -7s

Combine like terms: 7s + -7s = 0
10 + -2s = -7 + 0
10 + -2s = -7

Add '-10' to each side of the equation.
10 + -10 + -2s = -7 + -10

Combine like terms: 10 + -10 = 0
0 + -2s = -7 + -10
-2s = -7 + -10

Combine like terms: -7 + -10 = -17
-2s = -17

Divide each side by '-2'.
s = 8.5

Simplifying
s = 8.5

See similar equations:

| 30-3n=2(6-3n) | | 65=2y-5 | | x^2+14x-176=0 | | .9(y+1.4)=-1.8 | | -8t=n+v | | f(x)=2x^2+4x+1.5 | | -8(-7-5n)=-32-4n | | 13j+52=1 | | 8x=14+1x | | -59=5(1-8x)-7(1-3x) | | 21=15-r | | 30*15=x | | 3+9n=22 | | 5(3x+7)=3(7+8x) | | 3(8+6v)+8=-40+6v | | 4(1-7a)=88 | | 10c^2+29c-21=0 | | 11m+13=m+24 | | 9j+5=67 | | 90=5(-2-5n) | | 20y^2+17y+3= | | 7-3x=x+-4(2+x) | | x^2+14x-182=0 | | 9j+5=30 | | 2(-8x+6)=-84 | | -7(2x+8)=-126 | | 9=17u-8u | | 10v^2+43v-9=0 | | 5x-18=2(4x-15) | | 9+5=67 | | 3xy+2y+1=5+6y | | ln(y)=ln(x+C) |

Equations solver categories